Effect of laser heating on mechanical properties, residual stresses and retardation of fatigue crack growth in AA2024. Issue 4 (27th December 2020) - Kashaev, Nikolai; Groth, Anne; Ventzke, Volker; Horstmann, Manfred; Riekehr, Stefan; Staron, Peter; Huber, Norbert
Abstract: Local laser heating treatment using a defocussed laser beam was applied to the surface of 2‐mm‐thick AA2024‐T3 sheets. Two different treatment designs—namely, lines and circles—as well as the positioning and number of treatments were investigated regarding their potential to retard the propagation of through‐thickness fatigue cracks. The highest fatigue crack growth life extension of 285% was achieved by the application of four laser heating lines or two circles on each specimen side. The induced compressive residual stress field through the LH process is primarily responsible for an improvement in fatigue crack growth life. An emphasis was placed on investigating the effect of the treatment on the possible reduction of tensile and fatigue strength (S‐N life). If only one line was applied transverse to the loading direction or only one circle was used, the reduction of fatigue strength was comparable to the reduction of fatigue strength resulting from the stress concentration introduced due to the presence of a rivet hole.